IMPLEMENTASI PERJANJIAN TERAPEUTIK PENANGANAN COVID-19 JAMINAN PEMERINTAH DAN NON-PEMERINTAH DI RUMAH SAKIT ADI HUSADA UNDAAN WETAN SURABAYA: TINJAUAN DALAM PERSPEKTIF HUKUM PERDATA - Arawinda, Stella Hita; Suharto, R. Suharto; Triyono, Triyono (Diponegoro Law Journal, 2023)
Therapeutic Agreement is an agreement between a doctor and a patient that grants the doctor the authority to provide healthcare services to the patient based on the doctor's expertise and skills. Adi Husada Undaan Wetan Hospital in Surabaya, which is designated by the provincial government of East Java as one of the referral hospitals for COVID-19 patients, offers two types of Therapeutic Agreements for COVID-19 treatment: Government Assurance and Non-Government Assurance, each with its own advantages and disadvantages in terms of implementation. The purpose of this research is to provide an overview of the types of therapeutic agreements and their implementation in a specific hospital, as well as the legal sanctions that can be imposed by the authorities in the event of a violation of these agreements. The research method used is juridical-empirical, which involves interviews with the Head of the Medical Records Department at Adi Husada Undaan Wetan Hospital in Surabaya, as well as collecting legal materials such as legislation, Decisions of the Indonesian Ministry of Health related to COVID-19, journals, and books related to the research problem. The results of this study show that there are patient demands related to double claims and transfers of COVID-19 treatment, both from Government Assurance to Private Non-Government Assurance and vice versa. This is considered detrimental to the hospital because the payment mechanism for Government Assurance COVID-19 Treatment is through reimbursement from the Indonesian Ministry of Health. However, to address this issue, Adi Husada Undaan Wetan Hospital provides solutions such as closing the billing file upon the patient's request or novation, and offers to refer patients to other hospitals.